Propuesta para la implementación de un plan de seguridad y salud ocupacional para controlar los riesgos y reducir los accidentes en la división de mantenimiento de la empresa de servicio de agua potable y alcantarillado de La Libertad – Sedalib S.A - Tirado Medina, Jefferson Andrée (2017)
This research proposes an occupational health and safety plan in the maintenance division of La Libertad Drinking Water and Sewerage Service - SEDALIB SA, since in this division there is no proper occupational health and safety system Implemented or documented, to protect the integrity of its workers from any danger that threatens their health, minimizing and controlling the risks that may exist during working hours. The investigation was initiated with an actual diagnosis of the current situation of the entity and the maintenance division in the field of occupational health and safety, to identify the main risks and hazards that workers may be exposed; And to propose corrective and preventive measures in accordance with the law on occupational safety and health, its regulations and standards. After completing the analysis and research, a proposal for an occupational health and safety plan was developed for the SEDALIB maintenance division. This plan includes the internal regulations, IPERC matrix, contingency plan, annual health and safety program and safe work procedures. Finally, an economic evaluation of the proposed plan has been achieved and the economic indicators obtained are VAN = S /. 140.384.41 and TIR = 72%; which means that the implementation of the proposal is highly profitable